Histone Modifications as an Intersection Between Diet and Longevity - Molina-Serrano, Diego; Kyriakou, Dimitris; Kirmizis, Antonis (Frontiers in Genetics, 2019)
Histone modifications are key epigenetic regulators that control chromatin structure and gene transcription, thereby impacting on various important cellular phenotypes. Over the past decade, a growing number of studies have indicated that changes in various histone modifications have a significant influence on the aging process. Furthermore, it has been revealed that the abundance and localization of histone modifications are responsive to various environmental stimuli, such as diet, which can also affect gene expression and lifespan. This supports the notion that histone modifications can serve as a main cellular platform for signal integration. Hence, in this review we focus on the role of histone modifications during aging, report the data indicating that diet affects histone modification levels and explore the idea that histone modifications may function as an intersection through which diet regulates lifespan. A greater understanding of the epigenetic mechanisms that link environmental signals to longevity may provide new strategies for therapeutic intervention in age-related diseases and for promoting healthy aging.